2005
DOI: 10.1108/09556220510590948
|View full text |Cite
|
Sign up to set email alerts
|

Protective clothing – test methods and criteria of tear resistance assessment

Abstract: Purpose -The state-of-the-art of existing methods of tear resistance (static and dynamic) of clothing has been described, also presented are the parameters of static tear resistance for protective and work clothing depending on its application. Design/methodology/approach -For chosen group of fabrics the introduction of a new parameter of dynamic tear resistance was proposed. For research, five static tear test methods and the dynamic one were chosen. In order to find the relationship between the results of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Moreover, the described methodology in PN-EN ISO 469:2006/A1:2007(U) [33] for coated and non-coated fabrics on the tear strength is the same (the same sample shape and way of calculation), which enables the comparison of obtained results. It is worth noting that (as was shown in [18,19]) by this method we can obtain the lowest result of tear force (high level of the "safety coefficient"). It is important in the case of cotton protective clothing, which measured by this method of tearing can not fulfill this criterion.…”
Section: Protective and Work Clothingsupporting
confidence: 59%
See 1 more Smart Citation
“…Moreover, the described methodology in PN-EN ISO 469:2006/A1:2007(U) [33] for coated and non-coated fabrics on the tear strength is the same (the same sample shape and way of calculation), which enables the comparison of obtained results. It is worth noting that (as was shown in [18,19]) by this method we can obtain the lowest result of tear force (high level of the "safety coefficient"). It is important in the case of cotton protective clothing, which measured by this method of tearing can not fulfill this criterion.…”
Section: Protective and Work Clothingsupporting
confidence: 59%
“…In laboratory measurements, there are actually five standardized sample shapes. Research on the analysis of static tear strength methods and correlation between results of the tearing force obtained by different methods are presented elsewhere [17][18][19]. The methodology, as well as the way of calculating results, were unified.…”
Section: The Significance Of Static Tearing In the Light Of Standardsmentioning
confidence: 99%
“…In these RESEARCH applications fabrics are subjected to axial, tearing, wear and bursting loading conditions. Beata et al studied tearing strength of cotton blends with synthetic fibers under static and dynamic loading conditions and observed that weft direction having better tear strength than warp [5]. These woven fabrics were used to prepare composites using various polymers.…”
Section: Introductionmentioning
confidence: 99%
“…• an analysis of the existing tear resistance models and their possible application [1]; • a review of tear resistance parameters of produced cotton fabrics and assessment of particular measurement method utility for the determined textile assortment groups [1,2]; • an analysis of static tear resistance methods used in metrological laboratories [3,4]; • finding the significant common features and differences in behavior of samples, which underwent different tearing methods i.e. the characteristics of particular tearing methods dependent on the sample shape and tearing direction in relation to the tearing force [4]; • finding the relationship between the results obtained by different tearing methods, and the influence of a result calculation method on the mean tearing force [5]; • possibilities of elaboration of computer system for predicting the tear and tensile strength of cotton fabrics on the basis of introduced data concerning the component threads and fabric structure parameters.…”
mentioning
confidence: 99%